The Dutch Hatmakers of Late Medieval and Tudor London with an edition of their bilingual Guild Ordinances - McSheffrey, Shannon (Medieval and Renaissance Clothing and Textiles, 2023)
At the end of the Middle Ages, a group of hatmakers from the Low Countries migrated across the North Sea to London. These men brought with them new skills and technologies, unknown to English artisans, becoming the first to manufacture brimmed felts hats in England. However, though their wares were immediately popular with English consumers, from courtiers to ordinary people, they faced an economic environment in London that restricted and sometimes completely disallowed the production and retail of their goods. In the early years of the sixteenth century, the hatmakers' desire to remain independent from regulation and governance by London civic guilds led to their formation of a craft association of their own. The Hatmakers' fraternity of St James operated for about a decade, until in 1511 the royal council mandated their amalgamation with and subordination to the powerful London Haberdashers' Company. In their short period of independence, the Hatmakers' guild wrote bilingual ordinances, in English and Dutch, regulating the craft of hatmaking in London. The small parchment booklet in which they wrote the ordinances, now housed in the London Guildhall Library, contains more than a simple list of craft rules: it reveals how these Dutch craftsmen negotiated their immigrant lives in both the specifics of their artisanal practice and the broader social and linguistic realities of their daily interactions. This book, uniting historical and philological approaches, uncovers the remarkable lives and writings of these tradesmen, showing how they adapted to their new environment and reacted to the challenges they faced. It also presents a modern edition of the texts of the Hatmakers' guild book. Open Access to this volume will be available under the Creative Commons License: CC BY-NC-ND